Prodromus of a fern flora for Bolivia. XXVII. Pteridaceae - Kessler, Michael; Smith, Alan R.; Prado, Jefferson (Phytotaxa, 2017)
We provide a synopsis to the Pteridaceae s.l. in Bolivia, a family comprising four subfamilies, 27 genera, and 154 species. These totals, approximating those for Dryopteridaceae and Polypodiaceae, make this one of the most genus-and species-rich families in Bolivia. New combinations are made for two species of Argyrochosma: A. flava and A. tenera. Eight species of Pteridaceae are considered endemic: Adiantum solomonii, A. squamulosum, Cheilanthes glutinosa, Eriosorus angustus, E. ascendens, E. madidiensis, Pteris boliviensis, and P. lellingeri.